What if Brazil Hadn't Floated the Real in 1999? - Carlos Viana de Carvalho; André D. Vilela (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2015)
We estimate a dynamic, stochastic, general equilibrium model of the Brazilian economy taking into account the transition from a currency peg to inflation targeting that took place in 1999. The estimated model exhibits quite different dynamics under the two monetary regimes. We use it to produce counterfactual histories of the transition from one regime to another, given the estimated history of structural shocks. Our results suggest that maintaining the currency peg would have been too costly, as interest rates would have had to remain at extremely high levels for several quarters, and GDP would have collapsed. Accelerating the pace of nominal exchange rate devaluations after the Asian Crisis would have lead to higher inflation and interest rates, and slightly lower GDP. Finally, the first half of 1998 arguably provided a window of opportunity for a smooth transition between monetary regimes.
Keywords: E52; F41; 330; monetary policy; regime shift; currency peg; inflation targeting; Brazil